The significant factors that influence tenants' perceptions in renting a house / Siti Khalijah Ag Anuar and Maszuwita Abdul Waha - Ag Anuar, Siti Khalijah; Abdul Waha, Maszuwita (2021)
Tenant means a person who occupies land or property rented from a landlord, however tenants' perceptions in renting a house has drifted into oblivion. People will confuse in renting or buying a house if did not understand differentiate between renting and buying. So, this issue should be research to completely comprehend the significant factors that influence the tenants' perceptions in renting a house. The most important factors that influence tenants' perceptions in renting a house is home ownership become inaccessible for today's generation. This is because majority tenants are working adults and needed face to the insurmountable employability and changing social issues affecting its investment. All the data in this research was acquired from the results of demographic analysis and 100 sets of questionnaires within quantitative standards which conducted online through the Google Forms. The finding has been concluded after gather all the data, which is to identify the important factors in house renting and its chronological ranks to get the insight to rent versus ownership decision-making from all walks of life but also of the current market needs. This study will let the developer and researchers can provide appropriate pricing and amenities, reduce vacant properties and also realistic solutions such as the Rent to Own scheme, ultimately benefiting the clientele and property industry in the long run.